Mastering Functional Programming: Functional Techniques for Sequential and Parallel Programming with Scala - Kmetiuk, Anatolii (Packt Publishing, Limited, 2018)
In large projects, programmers tend to get overwhelmed by their complexity. It can be hard to keep track of all the interdependencies in the code-base and how its state changes on runtime. The solution to these problems is Functional Programming, a paradigm specifically designed to deal with the complexity of software development. Mastering.